Fused imidazoles as potential chemical scaffolds for inhibition of heat shock protein 70 and induction of apoptosis. Synthesis and biological evaluation of phenanthro[9, 10-d]imidazoles and imidazo[4, 5-f][1, 10]phenanthrolines. Issue 16 (1st April 2016) - Patel, Alpa; Sharp, Swee Y.; Hall, Katelan; Lewis, William; Stevens, Malcolm F. G.; Workman, Paul; Moody, Christopher J.
Abstract : Fused imidazoles inhibit growth of human cancer cell lines, and the Hsp70 pathway in cells, and induce apoptosis. Abstract : The imidazole ring is widespread in biologically active compounds, and hence imidazole-containing scaffolds are useful starting points for drug discovery programmes. We report the synthesis of a series of novel imidazole-containing compounds fused with either phenanthrene or phenanthroline, which show enhanced growth inhibitory potency against human colon, breast and melanoma cancer cell lines, as well as evidence of inhibition of the molecular chaperone heat shock protein 70 (Hsp70) pathway in cells, as shown by depletion of downstream oncogenic client proteins of the Hsp90 chaperone pathway, and induction of apoptosis.